PENERAPAN SISTEM MANAJEMEN MUTU UNTUK MENINGKATKAN EFISIENSI OPERASIONAL TRANSJAKARTA - Adela Netania Sihotang; Talitha Evania, Dinda Citra Azzahra, Ararya Athaya Wicaksana (CV. ADIBA AISHA AMIRA, 2024)
Quality Management System (QMS) is a structured and systematic approach to improving the quality of products and services. The implementation of QMS in Transjakarta has the potential to improve operational efficiency, leading to increased customer satisfaction and reduced costs. This study aims to describe the implementation of QMS in Transjakarta and its impact on operational efficiency. The research method used is a literature study with a qualitative approach. Data were collected based on relevant library sources. The results of the study indicate that Transjakarta has implemented QMS based on the ISO 9001:2015 standard. The implementation of QMS has had a positive impact on operational efficiency, as indicated by increased operational efficiency, improved quality in Transjakarta, decreased number of customer complaints, and decreased operational costs. This study also recommends that Transjakarta continue to strengthen the implementation of QMS to achieve optimal operational efficiency.